2019
DOI: 10.1177/0003319718822625
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Bone Markers in Diagnosis and Risk Stratification of Patients With Coronary Artery Disease

Abstract: Molecules that govern bone metabolism, such as osteoprotegerin (OPG) and osteopontin (OPN), have been isolated from other tissues, including blood vessels. Atherosclerosis and coronary artery disease (CAD) are leading causes of mortality worldwide. Despite novel biochemical and imaging techniques, early detection of CAD is still unsatisfactory. Experimental data indicate that bone turnover markers (BTMs) contribute to the development of atherosclerosis. This finding has sparked interest in their clinical use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 97 publications
(142 reference statements)
0
17
0
Order By: Relevance
“…Indeed, the contribution of bone metabolism markers such as OPG or osteopontin has been previously shown to serve as surrogate markers for CVD. 4 Moreover, OPGdeficient mice displayed increased atherosclerosis, vascular calcification and osteoporosis together with heightened circulating RANKL levels. 5 A candidate molecule which attracted particular attention in recent years is 25(OH) vitamin D 3 , due to pleiotropic functions extending beyond bone mineralisation and calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the contribution of bone metabolism markers such as OPG or osteopontin has been previously shown to serve as surrogate markers for CVD. 4 Moreover, OPGdeficient mice displayed increased atherosclerosis, vascular calcification and osteoporosis together with heightened circulating RANKL levels. 5 A candidate molecule which attracted particular attention in recent years is 25(OH) vitamin D 3 , due to pleiotropic functions extending beyond bone mineralisation and calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the contribution of bone metabolism markers such as OPG or osteopontin has been previously shown to serve as surrogate markers for CVD. 4 Moreover, OPG-deficient mice displayed increased atherosclerosis, vascular calcification and osteoporosis together with heightened circulating RANKL levels. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Human studies and transgenic mouse models have shown that increased osteopontin production, especially in myocytes, was associated with increased apoptosis and myocardial dysfunction [ 13 ]. Experimental studies have indicated that osteopontin played an important role in atherosclerosis development, vascular remodeling, and restenosis [ 2 , 14 , 15 , 16 ]. It has also been shown that atherosclerosis modifying therapies with statins or angiotensin II inhibiting drugs reduced circulating osteopontin levels [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, osteopontin thus functions beyond those related to bone formation. Osteopontin has been implicated in several physiological and pathological processes such as bone turnover [ 2 ], cell survival [ 3 ], immune regulation and response [ 4 ], inflammation [ 5 ], ischemia [ 6 ], tissue remodeling [ 7 ], tumor progression [ 8 ], and wound healing [ 9 ]. In inflammation, osteopontin acts as a proinflammatory cytokine, modulating the immune response by enhancing expression of Th1 cytokines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In atherosclerotic plaques, elevated OPG mRNA and protein levels were observed [ 3–5 ]. Several observational studies found that serum levels of OPG were independently correlated with the presence and severity of CAD after adjusting for traditional risk factors such as hypertension and smoking in logistic regression models [ 8 , 10 , 11 ]. Moreover, increased OPG levels strongly predicted adverse clinical outcomes in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%